Low DHEAS Concentration in a Girl Presenting with Short Stature and Premature Pubarche: A Novel PAPSS2 Gene Mutation - BEREKET, ABDULLAH; ELTAN, MEHMET; KAYGUSUZ, SARE BETÜL; DEMİRCİOĞLU, SERAP; KIRKGÖZ, TARIK; GÜRAN, TÜLAY (KARGER, 2020)
Objective: Dehydroepiandrosterone (DHEA) sulfotransferase (SULT2A1) converts DHEA to DHEA sulfate (DHEAS) which prevents bioactive androgen excess. This enzymatic reaction requires PAPS (3 '-phospho-adenosine-5 '-phosphosulfate) biosynthesis mediated by PAPS synthase 2 (PAPSS2). Here, we report a patient presenting with short stature and premature pubarche due to a novel homozygous mutation in the PAPPS2 gene. Case Report: A 7.5-year-old girl was referred for short stature. She was born at term with a birth weight of 2,850 g and her parents were first cousins. At presentation, her height was 113.0 cm (-2.1 SDS) and weight was 28.3 kg (+0.9 SDS), her arm span was 115.0 cm, and upper to lower segment ratio was 1.2. Her pubic hair and breast development were at Tanner stage III and I, respectively. Radiographs revealed mild lumbar scoliosis and platyspondyly and irregular vertebral endplates in the thoracolumbar region. Her serum DHEAS was low (39 ng/mL). The plasma DHEAS/DHEA ratio was significantly decreased on 2 separate measurements (4.4 and 19.8; normal range 31-345). PAPSS2 gene analysis identified a homozygous p.L440Wfs*12 (c.1318_1330 delCTACTACACCCTC) variant. This is the first report of a large deletion leading to a frameshift effect in the PAPSS2 gene and a truncated PAPSS2 protein. Conclusion: We describe the third case with PAPSS2 deficiency presenting with premature pubarche, and the first large deletion in the PAPSS2 gene. Although PAPSS2 deficiency is a rare cause of premature pubarche and adrenal androgen excess, it should be considered, especially in cases with disproportionate short stature and clinical hyperandrogenism associated with low plasma DHEAS concentration.
Keywords: Autosomal recessive brachyolmia; Premature pubarche; Spondyloepimetaphyseal dysplasia; PAPSS2; AUTOSOMAL RECESSIVE FORM; SPONDYLOEPIMETAPHYSEAL DYSPLASIA